A review of mobile applications for diabetes: could it replace the role of professional health care? - Lusy Noviani; Ajeng Diantini; Anas Subarnas (Journal of Global Pharma Technology, 2020)
Background: The prevalence of diabetes is increasing year to year, despite various attempts to reduce prevalence have been made. The role of professional health teams (PHTs) is critical to manage diabetes progression. Advances in technology such as Mobile Applications (MA) have provided new opportunities to support the success of diabetes treatment. This article aims to provide a critical analysis of the challenges that are not fully fulfilled and highlights directives for future research that can enhance the implementation of MA in diabetes management. Methods: A systematic review has been conducted. A number of articles related to mobile applications and diabetes mellitus published between 2011-2020 have been taken from Google Scholar, PubMed, and Medical ProQuest, and 15 articles were selected based on criteria set. Results: Each study appears to have different features in design MA, affecting the results varied in the 15 studies reviewed. Mobile technology-based applications demonstrated their role in improving communication, being accessible, facilitating self-management processes, improving compliance with treatment, and ultimately improving blood sugar control. Conclusion: The role of PHTs is important for the successful implementation of the fast-developing sensor and transfer app in the medical sector. It is the role of a PHTs to select adequate devices, apply them, and earnestly analyse their effectiveness and economic feasibility.